The Influence of Financial Literacy, Return Perception, and Risk Perception on Students' Investment Interest in Business Administration Upn "Veteran" East Java - Desi Anila; Acep Samsudin (Value Added : Majalah Ekonomi dan Bisnis, 2026)
The growth in the number of student investors at UPN "Veteran" East Java is not always accompanied by an adequate understanding of investment. Many students invest because of academic demands or trends, rather than based on interests that are supported by sufficient knowledge. This study aims to analyze the influence of financial literacy, return perception, and risk perception on the investment interest of Business Administration students. The study used an associative quantitative approach with 86 respondents selected through proportionate stratified random sampling technique. Data were collected using a Likert scale questionnaire  and analyzed by multiple linear regression using SPSS 25. The results of the study show that financial literacy, return perception, and risk perception simultaneously have a significant effect on investment interest. Partially, financial literacy, return perception, and risk perception have a positive and significant effect, respectively. The results of the determination coefficient showed that 48.4% of the variation in investment interest was explained by these three variables.